2015
DOI: 10.5455/jice.20150623090040
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine use among Turkish patients with chronic diseases

Abstract: Aim:Complementary and alternative medicine (CAM) is commonly used all over the world, and herbal medicines are the most preferred ways of CAM. The aim of this study was to determine the frequency of herbal medicine use among patients with chronic diseases.Methodology:A cross-sectional descriptive study was conducted from April 2014 to December 2014 among patients who had been diagnosed with diabetes mellitus (DM), hypertension (HT), and hyperlipidemia (HL) in Family Medicine Department of Dışkapı Yıldırım Beya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 22 publications
2
44
1
2
Order By: Relevance
“…About 80% of the human population in Ethiopia is said to be dependent on traditional medicine for primary healthcare services and most of this comes from plants [ 7 ]. Moreover, prevalence of chronic illnesses in the nation is increasing [ 8 ] and previous studies showed that the use of herbal remedies among such patients is very high [ 9 ]. Thus, pharmacists in Ethiopia are required more than ever to improve their role as experts of herbal medicines and in providing appropriate information to clients.…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of the human population in Ethiopia is said to be dependent on traditional medicine for primary healthcare services and most of this comes from plants [ 7 ]. Moreover, prevalence of chronic illnesses in the nation is increasing [ 8 ] and previous studies showed that the use of herbal remedies among such patients is very high [ 9 ]. Thus, pharmacists in Ethiopia are required more than ever to improve their role as experts of herbal medicines and in providing appropriate information to clients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies have generally revealed that the rate of using plants and herbal products was higher in patients with chronic diseases. 7,27 It was also shown in this study that, the students used medicinal herbs and herbal products in order heal their diseases and for their health. Zimmerman stated that plant supplements were getting increasingly popular around the world, in preventing diseases and improving wellness.…”
Section: Discussionmentioning
confidence: 58%
“…Çalışmamıza göre; bir yıldan daha az zamandır hiperlipidemi tanısı almış olan bireylerin ilaç dışı yöntem kullanım oranı daha uzun süredir tanılı olan bireylerden daha yüksek bulunmuştur. Hastaların, başlangıçta ilaç tedavisi yerine bitkisel yiyecekler başta olmak üzere alternatif yöntemler denemekte, fayda görmezse ilaç tedavisini tercih etmekte olduğu gözlendi (11).…”
Section: Discussionunclassified